CUSTOMER RELATIONSHIP MANAGEMENT MODEL FROM STRATEGIC APPROACH: A KNOWLEDGE MANAGEMENT PERSPECTIVE - Abdul Baist, Asma Tahir, Mumtaz Muhammad Khan & Muhammad Arshad (International Journal of Research Science and Management, 2018)
Purpose: To review the literature on Customer Relationship Management (CRM), identify the CRM models presented by different researchers. This paper considers CRM as a philosophy that can be translated into a strategy. An insight in the core components of CRM systems leading to inclusion of Tacit Knowledge (TK) can bring better understanding of marketing functioning. This understanding results in better decisions. Design/methodology/approach: A review of more than 200 papers on CRM, marketing, relationship marketing and Knowledge Management (KM) directed the attention towards the CRM research models and revealed the proposal to integrate CRM with KM for transformation of CRM into a strategic approach. Findings: A review of CRM models highlighted their Information Technology (IT) focus and directed the need for empirical validation, human involvement and specifically, that of knowledge with focus on TK. Research limitations/implications: This study is conceptual, based on exploration of critical review of literature. Practical implications: This exploratory study helps in understanding the primary and secondary components of CRM, integration of KM (specially TK) into CRM, its impact on successful CRM implementation, resultantly informed marketing decision making and improved organization performance. Originality/value: This paper stands out to explore CRM as a basis for strategic decision making wherein knowledge especially TK is a strategic enabler in which human involvement can lead to successful CRM implementation and better organization performance.